Principles for organizing the architectural environment of arctic cities using the example of Vorkuta (Russia) - Vabishchevich Daria; Ivanov Igor; Datsuk Tamara (E3S Web of Conferences, 2020)
The paper discusses the principles for organizing the architectural environment of Arctic cities using the example of Vorkuta, (Russia). The subject of the study is the architectural environment of Vorkuta and the influence on its formation of various groups of factors - climatic, psychological and environmental. Based on the study of the history of the appearance of the city and its condition today, the prospects of the region are assessed, and the main development vectors are identified. As a result of a comprehensive analysis of external factors and development prospects, the principles of organizing the architectural environment at different levels are formulated: urban planning level - the city and the quarter, architectural and planning level - the building. The principles of a possible organization of Vorkuta architectural environment are systematized, both in terms of impact levels and certain factors of influence, which are most significant for the region. The architectural environment of the city, created in the image of the cities of central Russia, was not adapted to the harsh northern climatic conditions. Studying the influence of various external factors on the urban environment will help formulating a conceptual scheme of the organization. In the future, it will prevent mistakes and contribute to the development of the city.